3-Hydroxy-2-phenyl-4(1H)-quinolinones as promising biologically active compounds - Hradil, P; Hlavác, J; Soural, M; Hajdúch, M; Kolár, M; Vecerová, R (Mini reviews in medicinal chemistry, 2009)
2-Phenyl-3-hydroxy-4(1H)-quinolinones can be considered as aza-analogues of flavones, compounds which are known for the wide-range of their biological activity. These quinolinones were studied as inhibitors of topoisomerase, gyrase and IMPDH. They were tested for anticancer activity in-vitro and were also shown to possess immunosuppressive properties. This review is the first summarizing the synthesis and activity of the mentioned quinolinones.
Keywords: Antineoplastic Agents; Quinolones; antibakteriální látky; Microbial Sensitivity Tests; Bacteria; inhibiční koncentrace 50; lidé; protinádorové látky; Anti-Bacterial Agents; Inhibitory Concentration 50; Humans; chinolony; mikrobiální testy citlivosti